1998
DOI: 10.1086/515885
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Maintenance Costs in an Anuran (Rana catesbeiana) Exposed to a Mixture of Trace Elements during the Embryonic and Early Larval Periods

Abstract: We investigated the relationship between maintenance costs (standard metabolic rates, measured as O2 consumption at rest) in tadpoles of the bullfrog, Rana catesbeiana, and exposure to contaminants in a coal ash-polluted habitat (characterized by a variety of trace elements). We compared metabolic rates of tadpoles collected from the polluted site with those from an unpolluted reference pond. Tadpoles collected in the polluted site had 40%-97% higher standard metabolic rates than those collected from the refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(104 citation statements)
references
References 0 publications
4
95
1
4
Order By: Relevance
“…The lack of effect on SMR contrasts previous work (Rowe et al 1998Hopkins et al 1999) in which other diverse organisms (bullfrogs, banded water snakes, and crayfish) collected from the ASH system exhibit SMRs (mL/g ⅐ h) approximately 23-32% higher than conspecifics from reference sites. Given that SMR is an indirect measure of an organism's maintenance costs, the elevated SMRs of other ASH organisms suggested that they incurred energetic costs, perhaps as a result of energy required to facilitate toxicant elimination or repair toxicant-induced cellular damage (Calow 1991).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The lack of effect on SMR contrasts previous work (Rowe et al 1998Hopkins et al 1999) in which other diverse organisms (bullfrogs, banded water snakes, and crayfish) collected from the ASH system exhibit SMRs (mL/g ⅐ h) approximately 23-32% higher than conspecifics from reference sites. Given that SMR is an indirect measure of an organism's maintenance costs, the elevated SMRs of other ASH organisms suggested that they incurred energetic costs, perhaps as a result of energy required to facilitate toxicant elimination or repair toxicant-induced cellular damage (Calow 1991).…”
Section: Discussioncontrasting
confidence: 94%
“…Prior to statistical comparisons, the highest 50% of SMR values for each individual were excluded from the dataset. The upper 50% of measurements were excluded to ensure that periods of activity were not included in the estimation of SMR (Rowe et al 1998) because SMR is a measure of an organism's metabolic rate at rest. The mean of the remaining 50% of measurements was then used as an estimate of SMR for each individual.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Além disso, a exposição a contaminantes pode gerar alterações na massa de órgãos internos, como fígado e rins (Arrieta et al 2004). Contaminantes podem também gerar alterações no desenvolvimento e no metabolismo, malformações e problemas de respiração e locomoção, com consequente redução na capacidade de evitar predadores, disputar recursos e se reproduzir (Carey & Bryant 1995;Rowe et al 1998;Selvi et al 2003;Forson & Storfer 2006;Söderman et al 2007;Hayes et al 2010).…”
Section: Introductionunclassified